Repeated-sprint ability in Division I collegiate male soccer players: Positional differences and relationships with performance tests - Lockie, R. G.; Moreno, M. R.; Orjalo, A. J.; Stage, A. A.; Liu, T. M.; Birmingham-Babauta, S. A.; Hurley, J. M.; Torne, I. A.; Beiley, M. D.; Risso, F. G.; Davis, D. L.; Lazar, A.; et al. (The Journal of Strength and Conditioning Research, 2019)
Repeated-sprint ability (RSA) in essential for soccer. Important considerations when assessing RSA is whether there are differences between positions (defenders, midfielders, and forwards), and what physiological characteristics may contribute to RSA. This has not been assessed in collegiate male players. Eighteen Division I male field players from one school performed several performance tests. The RSA test involved 7 × 30-m sprints completed on 20-second cycles. Measurements included total time (TT), and performance decrement (percent change in time from the first to last sprint; PD). Subjects also completed tests of lower-body power (vertical [VJ] and standing broad jump [SBJ]); linear (30-m sprint; 0-5 m, 0-10 m, 0-30 m intervals) and change-of-direction (505) speed; and soccer-specific endurance (Yo-Yo Intermittent Recovery Test Level 2; YYIRT2). A one-way analysis of variance (p < 0.05) determined between-position differences, and effect sizes were calculated. Pearson's correlations (p < 0.05) calculated relationships between RSA TT and PD with the other tests. There were no significant between-position differences for any test. There were large effects for the faster right-leg 505 and greater YYIRT2 distance for midfielders compared with defenders and forwards. Nonetheless, no between-position differences in RSA TT and PD were documented. There were relationships between RSA TT and the VJ (r = -0.59), SBJ (r = -0.61), 0-10 m (r = 0.64) and 0-30-m (r = 0.83) sprint intervals. There were no significant correlations for RSA PD. Male field players from one collegiate soccer team can demonstrate similar RSA across different positions. Greater lower-body power and sprinting speed could augment RSA.